The function \( f(x)=\frac{4 x+7}{x-6} \) is one-to-one. a. Find an equation for \( f^{-1}(x) \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find the inverse function \( f^{-1}(x) \) for the function \( f(x) = \frac{4x + 7}{x - 6} \), we start by rewriting the equation with \( y \) in place of \( f(x) \): 1. Start with: \[ y = \frac{4x + 7}{x - 6} \] 2. Now, swap \( x \) and \( y \): \[ x = \frac{4y + 7}{y - 6} \] 3. To solve for \( y \), multiply both sides by \( (y - 6) \): \[ x(y - 6) = 4y + 7 \] 4. Distributing \( x \): \[ xy - 6x = 4y + 7 \] 5. Rearranging gives: \[ xy - 4y = 6x + 7 \] 6. Factor out \( y \): \[ y(x - 4) = 6x + 7 \] 7. Finally, solve for \( y \): \[ y = \frac{6x + 7}{x - 4} \] Hence, the inverse function is: \[ f^{-1}(x) = \frac{6x + 7}{x - 4} \] Now, let's verify our equation by checking both \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \): **Verification of \( f(f^{-1}(x)) = x \)**: 1. Substitute \( f^{-1}(x) \) into \( f \): \[ f\left(f^{-1}(x)\right) = f\left(\frac{6x + 7}{x - 4}\right) = \frac{4\left(\frac{6x + 7}{x - 4}\right) + 7}{\left(\frac{6x + 7}{x - 4}\right) - 6} \] 2. Simplifying the numerator: \[ 4\left(\frac{6x + 7}{x - 4}\right) + 7 = \frac{24x + 28}{x - 4} + 7 = \frac{24x + 28 + 7(x - 4)}{x - 4} = \frac{24x + 28 + 7x - 28}{x - 4} = \frac{31x}{x - 4} \] 3. Simplifying the denominator: \[ \frac{6x + 7}{x - 4} - 6 = \frac{6x + 7 - 6(x - 4)}{x - 4} = \frac{6x + 7 - 6x + 24}{x - 4} = \frac{31}{x - 4} \] 4. Putting it all together: \[ f\left(f^{-1}(x)\right) = \frac{\frac{31x}{x-4}}{\frac{31}{x-4}} = x \] **Verification of \( f^{-1}(f(x)) = x \)**: 1. Substitute \( f(x) \) into \( f^{-1} \): \[ f^{-1}(f(x)) = f^{-1}\left(\frac{4x + 7}{x - 6}\right) = \frac{6\left(\frac{4x + 7}{x - 6}\right) + 7}{\left(\frac{4x + 7}{x - 6}\right) - 4} \] 2. Simplifying the numerator: \[ 6\left(\frac{4x + 7}{x - 6}\right) + 7 = \frac{24x + 42}{x - 6} + 7 = \frac{24x + 42 + 7(x - 6)}{x - 6} = \frac{24x + 42 + 7x - 42}{x - 6} = \frac{31x}{x - 6} \] 3. Simplifying the denominator: \[ \frac{4x + 7}{x - 6} - 4 = \frac{4x + 7 - 4(x - 6)}{x - 6} =